2019
DOI: 10.1167/iovs.19-27230
|View full text |Cite
|
Sign up to set email alerts
|

Sectoral Differences in the Association of Optic Nerve Head Blood Flow and Glaucomatous Visual Field Defect Severity and Progression

Abstract: PURPOSE. To investigate sectoral differences in the relationship between optic nerve head tissue blood flow, anatomically corresponding visual field defect severity, and future progression. METHODS. This retrospective longitudinal medical chart review comprised 508 eyes of 319 open-angle glaucoma patients (mean deviation: À9.2 6 7.0 dB), followed for an average of 4.7 6 1.1 years; an average 11.7 6 3.7 visual field tests were performed. Average total deviation (TD) was calculated in the superior, central, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 64 publications
0
15
1
Order By: Relevance
“…2019; Kiyota et al. 2019; Kuroda et al. 2020), our study is the first to measure it in the sectors of Garway‐Heath (Garway‐Heath et al.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…2019; Kiyota et al. 2019; Kuroda et al. 2020), our study is the first to measure it in the sectors of Garway‐Heath (Garway‐Heath et al.…”
Section: Discussionmentioning
confidence: 94%
“…Using a variety of techniques, studies showed that the ocular circulation is altered in glaucoma (Michelson et al 1996;Grunwald et al 1998;Findl et al 2000;Yoshioka et al 2020), and that VF sensitivity is correlated with ocular perfusion levels (Resch et al 2011;Hwang et al 2012;Yarmohammadi et al 2016;Gardiner et al 2019;Kiyota et al 2019;Kuroda et al 2020). In particular, OCT angiography (OCTA) has recently emerged as a promising tool to assist glaucoma diagnosis and monitoring (Yarmohammadi et al 2016;Sakaguchi et al 2017;Kiyota et al 2018;Moghimi et al 2019;Liu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some subtypes of glaucoma might share this pathophysiology with non-arteritic anterior ischemic optic neuropathy [37]. Kiyota et al also reported that sleep apnea syndrome was significantly associated with lower blood flow at superior to temporal optic nerve head tissue [37]. Moreover, a previous report suggested a relationship between PA and sleep apnea syndrome [38].…”
Section: Plos Onementioning
confidence: 99%
“…Nonarteritic anterior ischemic optic neuropathy often involves the inferior visual field defects given that the upper anastomosis appears to be less proficient than the lower. Thus, some subtypes of glaucoma might share this pathophysiology with non-arteritic anterior ischemic optic neuropathy [37]. Kiyota et al also reported that sleep apnea syndrome was significantly associated with lower blood flow at superior to temporal optic nerve head tissue [37].…”
Section: Plos Onementioning
confidence: 99%